2008
DOI: 10.1016/j.tsf.2007.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-Transform Photocurrent Spectroscopy for a fast and highly sensitive spectral characterization of organic and hybrid solar cells

Abstract: and in P3HT/TiO 2 junctions after irradiation with E > 1.9 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…[ 16 ] Similar experiments on polyfl uorene-PCBM and polymerpolymer blends were performed. [17][18][19] The CT states could also be excited optically by subgap illumination, [20][21][22] and be observed by electroluminescence as a result of charge injection. [ 23 , 24 ] The commonly used names for CT states and complexes are diverse, either used alternatively or to defi ne special cases.…”
Section: Experimental Evidence For the Charge Transfer Statementioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 ] Similar experiments on polyfl uorene-PCBM and polymerpolymer blends were performed. [17][18][19] The CT states could also be excited optically by subgap illumination, [20][21][22] and be observed by electroluminescence as a result of charge injection. [ 23 , 24 ] The commonly used names for CT states and complexes are diverse, either used alternatively or to defi ne special cases.…”
Section: Experimental Evidence For the Charge Transfer Statementioning
confidence: 99%
“…The CT state can alternatively be populated by a direct excitation into a weak CT absorption band [ 21 ] -termed as ground state charge transfer complex [ 32 ] -or via nongeminate recombination of free polarons.…”
Section: Experimental Evidence For the Charge Transfer Statementioning
confidence: 99%
“…Vandewal et al found that a highly sensitive technique Fourier-transform photocurrent spectrum (FTPS) could be used to measure the PV EQE (EQE PV ) spectrum where the low energy CT absorption bands could be resolved. 63,96 This technique allows for the determination of E CT via EQE PV in the absorption range of the charge transfer state:…”
Section: Copyright ©2010 the American Physical Societymentioning
confidence: 99%
“…Study of structural changes induced by annealing has been done ). According to (Vandewal et al 2008), frequency dependence is not an issue in case of organic solar cells.…”
Section: Nanocrystalline Diamond Cis and Organic Semiconductorsmentioning
confidence: 99%